2020
DOI: 10.1093/mnras/staa3984
|View full text |Cite
|
Sign up to set email alerts
|

The mass of the Milky Way out to 100 kpc using halo stars

Abstract: We use a distribution function analysis to estimate the mass of the Milky Way (MW) out to 100 kpc using a large sample of halo stars. These stars are compiled from the literature, and the vast majority (${\sim } 98{{\ \rm per\ cent}}$) have 6D phase-space information. We pay particular attention to systematic effects, such as the dynamical influence of the Large Magellanic Cloud (LMC), and the effect of unrelaxed substructure. The LMC biases the (pre-LMC infall) halo mass estimates towards higher values, while… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(77 citation statements)
references
References 82 publications
4
73
0
Order By: Relevance
“…Although we do not see any strong evidence for such features in this sample (see Fig. 3 and associated discussion in Deason et al 2021), larger upcoming spectroscopic surveys such as WEAVE, DESI, and 4MOST will be able to better explore this possibility.…”
Section: Stellar Halo Substructurementioning
confidence: 60%
See 1 more Smart Citation
“…Although we do not see any strong evidence for such features in this sample (see Fig. 3 and associated discussion in Deason et al 2021), larger upcoming spectroscopic surveys such as WEAVE, DESI, and 4MOST will be able to better explore this possibility.…”
Section: Stellar Halo Substructurementioning
confidence: 60%
“…As explained in Erkal, Belokurov & Parkin (2020), if this disequilibrium is not accounted for, estimates of the Milky Way mass will be biased in the outer halo. We perform this correction and measure the Milky Way mass out to 100 kpc in a companion work (Deason et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Of these, the closest to our estimate is that of GC19, which has a virial mass of M 200 = 1.2 × 10 12 M . Interestingly, this is also the mass favoured by the recent analysis of stellar halo kinematics by Deason et al (2020).…”
Section: T H E L M C a N D T H E E S C A P E V E L O C I T Y O F T H E M Wmentioning
confidence: 77%
“…Using the Boylan-Kolchin et al (2013) phase space plot, Hammer et al (2020) showed that Gaia DR2 orbits might indicate a passage more recent than 4 Gyr ago for many dSphs, assuming a total mass of 8.66 × 10 11 M for the MW (Eilers et al 2019). Because MW dSphs also have a peculiar planar alignment (Pawlowski et al 2014), Deason et al (2021 opted to use halo stars. After a thorough analysis of the possible recent accretions based on phase-space diagrams, they derived a total mass within 100 kpc of 6.07 × 10 11 M 2 , with which they associated systematics up to 1.2 × 10 11 M .…”
Section: Limitations Of This Study and Comparison With Other Workmentioning
confidence: 99%